Office 2010 just the steps for dummies - Marmel, Elaine J. (Hoboken, NJ : Wiley, 2010)
" ... How to convert older documents to Word 2010 ; Steps for printing documents ; Tips for working with Excel cells ; How to create formulas ; Elements you can add to a PowerPoint slide ; How to create an e-mail distribution list ; How to work in Backstage View ..."--Page 4 of cover
Word -- Excel -- PowerPoint -- Outlook -- Using office products together.
Includes index.
Print version record.
John Wiley and Sons
Keywords: Microsoft Office; Microsoft Office; Business -- Computer programs; COMPUTERS -- Desktop Applications -- Suites; COMPUTERS -- Enterprise Applications -- General; Business -- Computer programs